The Role of Riparian Vegetation in Pollutant Filtration and Sediment Stabilization in Lake Tondano, Indonesia - Wiesye Nangoy; Gerry Harindah; Rievo Djarang; Utari Satiman (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2026)
Riparian vegetation plays a crucial role in maintaining aquatic ecosystem stability by acting as a natural buffer against anthropogenic pollution and erosion. This study analyzed the composition, structure, and ecological functions of riparian vegetation in Lake Tondano, North Sulawesi, Indonesia, with emphasis on pollutant filtration and sediment stabilization. Field surveys were conducted from May to August 2025 at ten riparian stations surrounding Lake Tondano (4,638 ha). Vegetation sampling used a stratified line transect method with fifty plots of varying sizes according to vegetation strata. Quantitative analysis included relative abundance, frequency, dominance, Importance Value Index (IVI), and the Shannon–Wiener diversity index (H’). Ecological functions were assessed through correlations between vegetation structure and reported nutrient and sediment reduction efficiencies from tropical riparian studies. A total of fifteen dominant riparian species were identified, mainly from the families Poaceae and Cyperaceae. Cyperus papyrus (IVI = 21.81%) and Metroxylon sagu (IVI = 29.65%) functioned as key ecological species, while Ficus septica showed the highest IVI (90.83%), indicating strong structural dominance. The Shannon–Wiener diversity index (H’ = 2.65) reflects moderate to high diversity. Riparian vegetation was estimated to reduce nutrient loads by 40–60% and erosion by 30–50%, highlighting its importance for ecosystem-based lake management.